Instructional leadership and teacher self-efficacy for school improvement: A systematic review of empirical studies - Shihui Hua; Azlin Norhaini Mansor; Khairul Azhar Bin Jamaludin (Environment and Social Psychology, 2025)
This study addresses a crucial aspect of school success in the context of current educational reforms by methodically examining how instructional leadership indirectly affects student outcomes through teacher self-efficacy. In order to synthesise methodological approaches, research trends, and conceptual frameworks across various educational contexts, bibliometric mapping and qualitative content analysis were integrated into a systematic literature review of 34 peer-reviewed empirical studies published between 2015 and 2025, adhering to PRISMA 2020 guidelines. The results demonstrate that by defining school missions, overseeing instructional programs, and creating a supportive learning environment, instructional leadership raises teacher self-efficacy and boosts teachers' confidence in their ability to deliver instruction, manage the classroom, and engage students. Although the review shows a preponderance of quantitative designs, a narrow cross-cultural breadth, and a dearth of longitudinal and mixed-methods research, which limit subtle contextual insights, these processes do contribute to increased student accomplishment. The report offers evidence-based suggestions for leadership development programs that aim to improve student learning outcomes by increasing teacher efficacy. In addition to highlighting methodological and contextual priorities for future research, this review adds originality and value to the field by providing an integrative conceptual framework that elucidates the psychological processes connecting instructional leadership to educational outcomes.